HISTORY AND STUDY OF THE DEVELOPMENT OF CREATIVE STYLES IN UZBEK LITERATURE BY A MODERN ENGLISH AUTHOR - Mamajanova, Guncha (Журнал иностранных языков и лингвистики, 2023)
Our article presents research on the influence of modern English romance on the development of creative styles in Uzbek literature.